Analisa Performansi Jaringa 4G di Wilayah Malang - Nidya Suroyya (Politeknik Negeri Malang, 2019)
The implementation of LTE in Indonesia has experienced problems, especially in maintaining the performance of radio networks due to the increasing number of users and less than optimal coverage quality. This research will conduct an analysis of the performance of the 4G LTE network with a case study in the area around Jalan Jend. Basuki Rachmat and Malang City Station. The Key Performance Indicator (KPI) parameters used to measure the performance of the 4G LTE network in this study include RRC setup success rate, ERAB setup success rate, and Call setup success rate Accessibility, call drop rate (VoiP), service drop rate (all). Retainability, handover, Throughput and Radio Frequency (RF), data obtained from drive tests and statistical data.From the standard KPI data for the Drive test area, Jend.basuki Rachmat has a value above -100 dBm, the percentage of power transmitted is 100% with a download value of 98.83% throughput of more than 265 Mbps and an upload value of 100% throughputI of more than 265 Mbps. As well as the Malang City Station area has a value above -100 dBm, the percentage of transmitted power is 92.39% with a download value of 96.12% throughput of more than 265 Mbps and an upload value of 100% throughputI of more than 265 Mbps. The parameters of Accessibility, Retainability, Mobility, integrity and Radio Frequency (RF) must comply with KPI standards in order to get maximum performance according to user needs.